Genesis of the commodification of urban land in Pará and plans to expand the urban fabric to the cities of Santarém, Macapá and Cametá - Ventura Neto, Raul da Silva; Moura, Beatriz Mesquita (Risco - Journal of Architecture and Urbanism, 2021)
In the early twentieth century, the engineer João de Palma Muniz elaborates urban expansion plans for the main Pará cities, among them Cametá, Macapá and Santarém. The plans are directly influenced by hygienist ideology about the city, due to the formation of Palma Muniz at the Polytechnic School of Rio de Janeiro, the main center of diffusion of urban hygiene ideology in Brazil during the period. The article aims to analyze the institutional context that led to the elaboration of the plans of Cametá, Macapá and Santarém, influenced by the process of implementation of the Land Law of 1850 in Pará, and concludes with the morphological analysis of the predicted urban design. of the urban core of these three cities.